Military diasporas: building of empire in the Middle East and Europe (550 BCE-1500 CE) - Christ, Georg; Sänger, Patrick; Carr, Mike (Routledge, 2023)
Military Diasporas in an Achaemenid Perspective / Hilmar Klinkott, Kiel -- Immigrant Soldiers and Ptolemaic Policy in Hellenistic Egypt (Late Fourth Century-30 BCE): Reflections on a Military Diaspora and Its Components / Patrick Sänger -- Syrian Recruits and Units in the Roman Army: A Military Diaspora? / Nathanael Andrade -- Participants in the Emperor's Glory: The Statues for Generals in Late Antique Rome / Mariana Bodnaruk -- The Persian and Arab Occupations of Egypt in the Seventh Century / Lajos Berkes -- Alexios, Emperor of the Diasporas? Komnenian Revolt of 1081 and the Foreign Military Groups in Byzantium / Roman Shliakhtin -- The Catalan Company as a Military Diasporic Group in Medieval Greece / Mike Carr & Alasdair Grant -- Christian Expatriates in Muslim Lands: The Many Roles of Aragonese Mercenaries in Medieval Northern Africa / Nikolas Jaspert -- Professional Turks or Military Diaspora? The Mamluks and Dynamics of Ethnicity in Late Medieval Egypt and Syria / Julien Loiseau -- Stradioti: A Balkan Military Diaspora in Early Modern Europe / Nicholas C. J. Pappas -- Military Auxiliaries in Twelfth- and Thirteenth-Century Hungary: Nomads vs. Crusader Knights / László Veszprémy -- Medieval Queens and the Diaspora of Escort, Conquest, the Crusades and Military Orders / Christopher Mielke -- Encountering the Heathen on the Baltic Frontier: The Order of the Sword Brethren and the Teutonic Order in Thirteenth-Century Livoniai / Verena Schenk zu Schweinsberg -- A Military Diaspora in Medieval Christendom: The Teutonic Orderii / Mark Whelan -- The Cold Winter Campaign of 1511: Swiss Military Autonomy and Heteronomy during the Transalpine Campaigns /Anna Katharina Weltert and Georg Christ.
Enthält bibliografische Angaben und einen Index